Altered Processing of Visual Stimuli in Vestibular Migraine Patients Between Attacks: A Combined VEP and sLORETA Study - Liu, Jiahao; Zhang, Qi; Liang, Maojin; Wang, Yajing; Chen, Yuebo; Wang, Junbo; Li, Jiahong; Chen, Ling; Yu, Leyin; Cai, Yinglin; Zheng, Yiqing; Ou, Yongkang (Frontiers in Human Neuroscience, 2021)
Objective Vestibular migraine (VM) is one of the most common causes of recurrent vertigo, but the neural mechanisms that mediate such symptoms remain unknown. Since visual symptoms and photophobia are common clinical features of VM patients, we hypothesized that VM patients have abnormally sensitive low-level visual processing capabilities. This study aimed to investigate cortex abnormalities in VM patients using visual evoked potential (VEP) and standardized low-resolution brain electromagnetic tomography (sLORETA) analysis. Methods We employed visual stimuli consisting of reversing displays of circular checkerboard patterns to examine “low-level” visual processes. Thirty-three females with VM and 20 healthy control (HC) females underwent VEP testing. VEP components and sLORETA were analyzed. Results Patients with VM showed significantly lower amplitude and decreased latency of P1 activation compared with HC subjects. Further topographic mapping analysis revealed a group difference in the occipital area around P1 latency. sLORETA analysis was performed in the time frame of the P1 component and showed significantly less activity (deactivation) in VM patients in the frontal, parietal, temporal, limbic, and occipital lobes, as well as sub-lobar regions. The maximum current density difference was in the postcentral gyrus of the parietal lobe. P1 source density differences between HC subjects and VM patients overlapped with the vestibular cortical fields. Conclusion The significantly abnormal response to visual stimuli indicates altered processing in VM patients. These findings suggest that abnormalities in vestibular cortical fields might be a pathophysiological mechanism of VM.